Microstructures and mechanical properties of laser offset welded 5052 aluminum to press-hardened steel - Cao, Xiaobing; Zhou, Xiongfeng; Wang, Haoran; Luo, Zhi; Duan, Ji'an (Journal of materials research and technology, 2020)
The study to obtain a sound joint between aluminum and steel is rather challenging due to the large mismatch in thermal properties and the formation of brittle IMCs, especially for press-hardened steel attributing to its martensite microstructure. In this present study, dissimilar joining of 5052 aluminum and press-hardened steel was comprehensively explored by employing laser offset welding without any fillers and interlayers. The influence of laser offset on welding appearance and mechanical properties was evaluated. The microstructure analysis, bonding mechanism, and fracture behavior were identified and characterized by means of optical microscope (OM), scanning electron microscope (SEM), energy-dispersive X-ray spectrometer (EDS), and X-ray diffraction (XRD). The satisfactory welding appearance and mechanical property of 129.6MPa was obtained at the laser offset of 0.2mm. The interface microstructure was composed of continuous Fe2Al5, acicular Fe4Al13 and islands IMCs. In addition, micro cracks could be initiated spontaneously in Fe2Al5 layer due to the residual stress, whereas a consecutive crack seems be induced by a micro pore defect. No matter what the fracture mode was during tensile test, the fracture surface was localized at the welded interface.